SISTEM PEMESANAN DAN PENJUALAN TOKO ROTI PADA AMELIA CAKE BERBASIS WEBSITE - Nugroho Dwi Laksono (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2019)
Amelia cake is a home-based industry specializing in bread and located at perum griya purwantara a23 tukangan, randusari, teras, boyolali. Amelia cake is still using a conventional sales system with customers comes directly to the store and make payments. In addition, the promotion system still uses word of mouth (WOM) and distributes brochures.The aims of the research is to design a ordering website-based and sales system. Besides, it is also expected to help Amelia cake in marketing their products so Amelia cake can be known by the public. While, the system development method used the waterfall method. System testing used the blackbox method and questionnaire. Blackbox testing indicates that the website can run well. While, questionnaire testing with a total of 25 respondents obtained an average value of 3,32 with interpretation of strongly agree. In that case, the respondent statef strongly agree that website Amelia cake is accurate in convenyinf information and easy to operate.